2015
DOI: 10.1016/j.image.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Real-time event classification in field sport videos

Abstract: The paper presents a novel approach to real-time event detection in sports broadcasts. We present how the same underlying audio-visual feature extraction algorithm based on new global image descriptors is robust across a range of different sports alleviating the need to tailor it to a particular sport. In addition, we propose and evaluate three different classifiers in order to detect events using these features: a feed-forward neural network, an Elman neural network and a decision tree. Each are investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…A. O'Reilly, Whelan, Ward, Delahunt, & Caulfield, 2017b;Ó Conaire et al, 2010;Reily et al, 2017;Shah et al, 2007;Zhu et al, 2006). Other algorithms included kNN (n = 3) (Díaz-Pereira et al, 2014;Montoliu et al, 2015;Ó Conaire et al, 2010), decision tree (DT) (n = 2) (Kapela et al, 2015;Liao et al, 2003), RF (n = 2) (Kasiri-Bidhendi et al, 2015;Kasiri et al, 2017), and Multilayer Perceptron (MLP) (n = 2) (Kapela et al, 2015;Montoliu et al, 2015). Deep learning was investigated in seven studies (Bertasius et al, 2017;Ibrahim, Muralidharan, Deng, Vahdat, & Mori, 2016;Karpathy et al, 2014a;Nibali et al, 2017;Ramanathan et al, 2015;Tora, Chen, & Little, 2017;Victor et al, 2017) of which used CNNs or LSTM RNNs as the core model structure.…”
Section: Vision Recognition Model Development Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A. O'Reilly, Whelan, Ward, Delahunt, & Caulfield, 2017b;Ó Conaire et al, 2010;Reily et al, 2017;Shah et al, 2007;Zhu et al, 2006). Other algorithms included kNN (n = 3) (Díaz-Pereira et al, 2014;Montoliu et al, 2015;Ó Conaire et al, 2010), decision tree (DT) (n = 2) (Kapela et al, 2015;Liao et al, 2003), RF (n = 2) (Kasiri-Bidhendi et al, 2015;Kasiri et al, 2017), and Multilayer Perceptron (MLP) (n = 2) (Kapela et al, 2015;Montoliu et al, 2015). Deep learning was investigated in seven studies (Bertasius et al, 2017;Ibrahim, Muralidharan, Deng, Vahdat, & Mori, 2016;Karpathy et al, 2014a;Nibali et al, 2017;Ramanathan et al, 2015;Tora, Chen, & Little, 2017;Victor et al, 2017) of which used CNNs or LSTM RNNs as the core model structure.…”
Section: Vision Recognition Model Development Methodsmentioning
confidence: 99%
“…One study (Karpathy et al, 2014a) used the publicly available Sports-1M, as previously described. Vision-based studies also reported datasets in total time, 10.3 hours (Bertasius, Park, Yu, & Shi, 2017), 3 hours (Montoliu, Martín-Félez, Torres-Sospedra, & Martínez-Usó, 2015), 1, 500 minutes (Shah et al, 2007), and 50 hours (Kapela et al, 2015), and by frame numbers, 6, 035 frames (Zhu, Xu, Gao, & Huang, 2006) and 10, 115 frames (Reily et al, 2017).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In sports broadcasts the cameras and the camera viewpoint change frequently. For example, in a short period a camera might show the broad view of the field, followed by a close-up of the player and then move to crowd reaction [7]. Therefore in any sports analysis system, first the video is broken down into different shots, and then the shots are analysed to extract the structural information for that particular sport.…”
Section: Reviewmentioning
confidence: 99%
“…These treatments involve a large variety of complex techniques and necessitate high processing power. Real-time video content analysis and its integration in embedded systems are also becoming a focus of research [2,[4][5][6]. Video content analysis techniques are used in constrained applications [2,3] like real-time content delivery, interactive TV, * Correspondence: abdessalem.benabdelali@enim.rnu.tn surveillance systems, security systems, and personal video recorders.…”
Section: Introductionmentioning
confidence: 99%